DYNAMICS AND CURRENT STATE OF YOUTH CRIME IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2024)
The dynamics of crime is the increase or decrease of crime in general and its structural indicators within a certain period (month, quarter, half-year, year, five-year, ten-year, twenty-year, etc.). Many factors influence the dynamics of crime. The most important of them can be grouped into two groups: social factors and legal factors.
Keywords: dynamics; factors; crime; general